Evaluating the frequency of breast cancer risk factors in women referred to mammography center for breast cancer screening: A report from south part of Iran. (June 2018) - rahime, Zareh; Parwaie, Wrya; Farhood, Bagher; Afkhami Ardekani, Mahdieh; Safari, Hossein
Highlights: 1- The maximum frequency of age in women with their first mammogram ranged from 46 to 50 years old. 2- It seems necessary to design programs in order to educate women about methods of breast cancer screening. 3- Changes in lifestyle such as changing diet and pay more attention to physical activity can reduce the risk of breast cancer. Abstract: Background: This study aimed to evaluate the frequency of risk factors of breast cancer and assess the women' age referred to mammography center at first screening mammogram in Bandar Abbas county, Iran. Methods: A two-part questionnaire was used to gather the required data among 104 women who referred to the mammography center for the first time. The first part of the questionnaire was answered by patients and it included questions about age and effective parameters on breast cancer such as having breast pain and discharge, use of oral contraceptives, duration of breastfeeding, amount of daily exercise, and number of children. The second part of the questionnaire covered clinical questions regarding each of the patients and was filled by physicians after interpreting mammograms. Results: The maximum frequency of age in women with their first mammogram ranged from 46 to 50 years old. Furthermore, 82% of women did not feel mass in their breast. The percentage of women who complained of breast pain before attending to mammography center was 32%. Most of the participations had more than three pregnancies and were pregnant for the first time in ages less than 20. Benign mass was diagnosed in 89% of women having lesion and three women were suspected to have malignant mass. Conclusion: Due to the low performance of women in using screening methods such as mammography and breast self-examination, it seems necessary to design programs in order to educate women about methods of breast cancer screening. Also, it appears essential to establish changes in lifestyle such as changing diet and pay more attention to physical activity that can reduce the risk of breast cancer.